REKONSTRUKSI PEMIDANAAN KERJA SOSIAL PADA TINDAK PIDANA RINGAN SEBAGAI UPAYA PENCEGAHAN BERULANGNYA TINDAK PIDANA RINGAN DI INDONESIA - Ika Wahyu Setyawati (Criminal Law Section Faculty of Law Universitas Sebelas Maret, 2013)
AbstractAwareness of legal obligations are not solely related to the legal obligations of the provisions of the law, but also the unwritten law. Seeing the conditions that occur in today’s society, the writer can know that criminal sanctions in misdemeanor becomes less effective. It can be seen from the continued recurrence of minor criminal offenses and showed increasing trend. The emergence of an increasing trend of misdemeanor cases is caused by several factors, including the ineffectiveness of the function of providing a deterrent effect on criminal sanctions provided in the community and also the level of legal awareness of Indonesia is still relatively low. Therefore, the emphasis in this paper is whether the application of criminal sanctions for minor offenses outlined in the Code of Penal Code (Code) to run effectively? How does the formation of an appropriate model for social work criminal sanctions in cases of misdemeanor as recurrence prevention solutions misdemeanor cases in order to realize social justice.Keywords: misdemeanor, social work criminal